GENETIC VARIATION IN THREE BREEDS OF INDONESIAN LOCAL DUCKS BASED ON BLOOD AND EGG WHITE PROTEIN POLYMORPHISM - Johari, S.; Ekasari, S.; Kurnianto, E. (Diponegoro University, 2013)
A study of genetic variation of four blood protein loci and three egg white loci in three breeds ofIndonesian local ducks (Magelang duck = MAD, Tegal duck = TED and Mojosari duck= MOD) wasinvestigated by using polyacrilamide gel electrophoresis (PAGE). The result showed that four bloodprotein loci (Pre-albumin, Albumin, Transferrin and Post-transferrin) and three egg white loci(Ovalbumin, Ovoglobulin and Conalbumin) were found to be polymorphic in three breeds of localducks. There was no difference on blood and egg white protein polyimorphism. The average value ofheterozygosity on three breeds of local ducks had a genetic potential to determine the controlled matingsystem and selection to obtain pure line. The closest phylogenetic relationship among the three breeds oflocal ducks occurred between MAD and TED.